Physiopathological Aspects of Sellar Epidermoid Cyst Determining Endocrine Disturbances: A Case Report - Cambruzzi, Eduardo; Ferreira, Nelson Pires; Barcellos, Gabriel; Fruet, Pablo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Epidermoid cysts (ECs) of the central nervous system (CNS) constitute benign circumscribed lesions that are more common in lateral than in midline sites. Epidermoid cysts of the CNS arise more frequently in the cerebellopontine angle, around the pons, near the sella, within the temporal lobe, in the diploe, and in the spinal canal. Most common tumoral lesion of sellar region is pituitary adenoma, and sellar cystic epithelial masses may be difficult to differentiate based only on clinical and imaging findings. Epidermoid cysts are covered by keratinized squamous epithelium and are usually filled with keratin lamellae. The process is, for the most part, maldevelopmental in origin, presumably arising from trapped surface ectodermal elements in association with the developing CNS during the closure of the neural groove or formation of the secondary cerebral vesicles. In the present study, the authors describe a case of sellar epidermoid cyst producing endocrine alterations and visual disturbance in a 35 years woman, and review the physiopathological and diagnostic criteria of this lesion.
Keywords: epidermoid cyst; sellar region; pathology; central nervous system cysts; brain neoplasms